Fabric and textile product

The fabric, made from meta-type all-aromatic polyamide fibers and conductive fibers with a cationically dyeable polyester component, addresses the challenge of simultaneously achieving flame retardancy, antistatic properties, and appearance quality, ensuring effective performance even after multiple washes.

JP2025068220APending Publication Date: 2025-04-28TEIJIN LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023177977
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

Existing flame-retardant fabrics fail to simultaneously achieve high levels of flame retardancy, antistatic properties, and excellent appearance quality.

Method used

A fabric composed of meta-type all-aromatic polyamide fibers and conductive fibers, where the conductive fibers include a cationically dyeable polyester component, both fibers are colored, and the fabric maintains a specific frictional charge amount and flammability measurement.

Benefits of technology

The fabric achieves excellent flame retardancy, antistatic properties, and appearance quality, with maintained performance even after 25 washes, and is suitable for various textile products such as protective clothing and work clothes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068220000001
    Figure 2025068220000001
Patent Text Reader

Abstract

To provide a fabric and a textile product which are excellent in flame retardancy, antistatic properties, and appearance quality.SOLUTION: In a fabric containing a meta-type wholly aromatic polyamide fiber and a conductive fiber, the conductive fiber contains a cationic dyeable polyester ingredient, both of the meta-type wholly aromatic polyamide fiber and the conductive fiber are colored, and a triboelectric charge quantity measured by a JIS L1094-2014 C method is 3.5 μC / m2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fabric and a textile product which are excellent in flame retardancy, antistatic properties and appearance quality. [Background technology]

[0002] Conventionally, flame-retardant fabrics made of fully aromatic polyamide fibers (aramid fibers) have been used in clothing worn by firefighters, pilots, race drivers, and workers at power and chemical companies, etc., on the assumption that the clothing will come into contact with fire or high temperatures.

[0003] Since these textile products are required to have not only flame retardancy but also antistatic performance, it has been proposed to mix conductive fibers such as conductive aliphatic polyamide fibers (conductive nylon fibers) and conductive acrylic fibers into the fabric (for example, Patent Documents 1 to 4). By mixing conductive fibers into the fabric, static electricity generated by friction of the fabric can be reduced, and it is possible to prevent dust adhesion, harmful effects due to discharge, ignition in explosion-proof environments, etc. In addition, the use of conductive acrylic fibers can also provide excellent appearance quality. However, it is still not satisfactory in terms of flame retardancy, antistatic properties, and appearance quality. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 035638 Brochure [Patent Document 2] International Publication No. 2018 / 084040 Brochure [Patent Document 3] International Publication No. 2015 / 159749 Brochure [Patent Document 4] International Publication No. 2020 / 129746 Brochure Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above-mentioned background, and an object of the present invention is to provide a fabric and a textile product which are excellent in flame retardancy, antistatic properties and appearance quality. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to achieve the above object, and as a result have completed the present invention. Thus, according to the present invention, the following inventions are provided.

[0007] 1. A fabric comprising a meta-type wholly aromatic polyamide fiber and a conductive fiber, the conductive fiber containing a cationic dyeable polyester component, the meta-type wholly aromatic polyamide fiber and the conductive fiber being both colored, and having a triboelectric charge of 3.5 μC / m as measured by JIS L1094-2014 C method. 2 A fabric characterized in that: 2. The fabric according to claim 1, wherein the conductive fiber is a core-sheath type composite fiber, in which the core contains conductive particles and the sheath is made of cationic dyeable polyester that does not contain conductive particles. 3. The fabric according to 1 or 2 above, wherein the meta-type wholly aromatic polyamide fiber and the conductive fiber contain the same dye. 4. The fabric according to claim 3, wherein the dye is a cationic dye. 5. The fabric according to any one of 1 to 4 above, wherein the conductive fibers are contained in the fabric in an amount of 1 to 30 mass % based on the mass of the fabric. 6. The fabric according to any one of 1 to 5 above, wherein the meta-type wholly aromatic polyamide fiber and the conductive fiber are contained in the fabric as a blended yarn. 7. Fabric weight is 100-300g / m 2 The fabric according to any one of 1 to 6 above, wherein the range is within the range. 8. After 25 washes as specified in JIS L1930 C4 method, the amount of triboelectric charge measured by JIS L1094-2014 C method was 3.5μC / m 2 8. The fabric according to any one of 1 to 7 above, which is as follows: 9. The fabric according to any one of 1 to 8 above, which has an afterflame time of 1.0 second or less in a flammability measurement specified in JIS L1091-1992 A-4 method (12-second flame contact). 10. A textile product made using the fabric according to any one of 1 to 9 above, selected from the group consisting of protective clothing, work clothing, fireproof clothing, camouflage clothing, happi coats, and aprons. Effect of the Invention

[0008] According to the present invention, it is possible to obtain fabrics and fiber products which are excellent in flame retardancy, antistatic properties and appearance quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The embodiments of the present invention will be described in detail below. First, the meta-type wholly aromatic polyamide fiber used in the present invention is a fiber made of a polymer in which 85 mol % or more of the repeating units are m-phenylene isophthalamide. Such a meta-type wholly aromatic polyamide may be a copolymer containing a third component within the range of less than 15 mol %.

[0010] Such meta-type wholly aromatic polyamides can be produced by a conventionally known interfacial polymerization method. The degree of polymerization of the polymer is preferably in the range of 1.3 to 1.9 dl / g intrinsic viscosity (IV) measured in a 0.5 g / 100 ml N-methyl-2-pyrrolidone solution.

[0011] The meta-type wholly aromatic polyamide may contain an alkylbenzenesulfonate onium salt. Preferred examples of the alkylbenzenesulfonate onium salt include hexylbenzenesulfonate tetrabutylphosphonium salt, hexylbenzenesulfonate tributylbenzylphosphonium salt, dodecylbenzenesulfonate tetraphenylphosphonium salt, dodecylbenzenesulfonate tributyltetradecylphosphonium salt, dodecylbenzenesulfonate tetrabutylphosphonium salt, and dodecylbenzenesulfonate tributylbenzylammonium salt. Among them, dodecylbenzenesulfonate tetrabutylphosphonium salt or dodecylbenzenesulfonate tributylbenzylammonium salt is particularly preferred because it is easily available, has good thermal stability, and has high solubility in N-methyl-2-pyrrolidone.

[0012] In order to obtain a sufficient effect of improving dyeability, the content of the alkylbenzenesulfonic acid onium salt is preferably 2.5 mol % or more (more preferably 3.0 to 7.0 mol %) relative to the poly-m-phenyleneisophthalamide.

[0013] As a method for mixing poly-m-phenylene isophthalamide and an alkylbenzene sulfonate onium salt, a method of mixing and dissolving poly-m-phenylene isophthalamide in a solvent, and then dissolving an alkylbenzene sulfonate onium salt in the solvent, etc., can be used. The dope thus obtained is formed into fibers by a conventionally known method.

[0014] For the purpose of improving dyeability and resistance to fading, the polymer used for the meta-type wholly aromatic polyamide fiber may have an aromatic polyamide skeleton containing a repeating structural unit represented by the following formula (1) in which an aromatic diamine component different from the main structural unit of the repeating structure or an aromatic dicarboxylic acid halide component is copolymerized as a third component in an amount of 1 to 10 mol % relative to the total amount of the repeating structural units of the aromatic polyamide. -(NH-Ar1-NH-CO-Ar1-CO)- Formula (1) Here, Ar1 is a divalent aromatic group having a linking group in a meta-coordinated or non-parallel axial direction.

[0015] It is also possible to copolymerize a third component such as the following. Specific examples of the aromatic diamines shown in formulas (2) and (3) include p-phenylenediamine, chlorophenylenediamine, methylphenylenediamine, acetylphenylenediamine, aminoanisidine, benzidine, bis(aminophenyl)ether, bis(aminophenyl)sulfone, diaminobenzanilide, and diaminoazobenzene. Specific examples of the aromatic dicarboxylic acid dichlorides shown in formulas (4) and (5) include terephthalic acid chloride, 1,4-naphthalenedicarboxylic acid chloride, 2,6-naphthalenedicarboxylic acid chloride, 4,4'-biphenyldicarboxylic acid chloride, 5-chloroisophthalic acid chloride, 5-methoxyisophthalic acid chloride, and bis(chlorocarbonylphenyl)ether.

[0016] H2N-Ar2-NH2...Formula (2) H2N-Ar2-Y-Ar2-NH2... formula (3) XOC-Ar3-COX...Formula (4) XOC-Ar3-Y-Ar3-COX...Formula (5)

[0017] Here, Ar2 is a divalent aromatic group different from Ar1, Ar3 is a divalent aromatic group different from Ar1, Y is at least one atom or functional group selected from the group consisting of an oxygen atom, a sulfur atom, and an alkylene group, and X is a halogen atom.

[0018] The degree of crystallinity of the meta-type wholly aromatic polyamide fiber is preferably 5 to 35% in terms of good dye exhaustion and easy adjustment to a target color with less dye or under weak dyeing conditions, and more preferably 15 to 25% in terms of low surface uneven distribution of the dye, high resistance to discoloration, and dimensional stability required for practical use.

[0019] The amount of the remaining solvent in the meta-type wholly aromatic polyamide fibers is preferably 0.1 mass % or less (more preferably 0.001 to 0.1 mass %) so as not to impair the excellent flame retardant performance of the meta-type wholly aromatic polyamide fibers. The meta-type wholly aromatic polyamide fiber can be produced by the following method: In particular, the crystallinity and the amount of remaining solvent can be adjusted to the above ranges by the method described below.

[0020] The polymerization method for the meta-type wholly aromatic polyamide polymer is not particularly limited, and may be, for example, a solution polymerization method or an interfacial polymerization method described in JP-B-35-14399, U.S. Pat. No. 3,360,595, JP-B-47-10863, etc.

[0021] The spinning solution is not particularly limited. An amide-based solvent solution containing an aromatic copolyamide polymer obtained by the above-mentioned solution polymerization or interfacial polymerization may be used, or the polymer isolated from the above-mentioned polymerization solution and dissolved in an amide-based solvent may be used.

[0022] Examples of the amide solvent used here include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethylsulfoxide, etc. N,N-dimethylacetamide is particularly preferred.

[0023] The copolymerized aromatic polyamide polymer solution obtained as described above is stabilized by further containing an alkali metal salt or an alkaline earth metal salt, which allows use at a higher concentration and at a lower temperature, and is therefore preferable. The alkali metal salt and the alkaline earth metal salt are preferably 1% by mass or less (more preferably 0.1% by mass or less) based on the total mass of the polymer solution. In the spinning and coagulation step, the spinning solution (meta-type wholly aromatic polyamide polymer solution) obtained above is spun into a coagulation solution and coagulated.

[0024] The spinning device is not particularly limited, and a conventionally known wet spinning device can be used. In addition, the number of spinning holes, arrangement, hole shape, etc. of the spinneret are not particularly limited as long as it can perform stable wet spinning. For example, a multi-hole spinneret for staple fibers having 1000 to 30000 holes and a spinning hole diameter of 0.05 to 0.2 mm may be used. The temperature of the spinning solution (meta-type wholly aromatic polyamide polymer solution) when spun from the spinneret is preferably in the range of 20 to 90°C.

[0025] As the coagulation bath used to obtain the fibers, it is preferable to use an aqueous solution of an amide solvent, preferably NMP, containing substantially no inorganic salt and having a concentration of 45 to 60 mass%, with the bath temperature in the range of 10 to 50°C. If the concentration of the amide solvent (preferably NMP) is less than 45 mass%, the skin will be thick, which may reduce the washing efficiency in the washing step and make it difficult to reduce the amount of solvent remaining in the fibers. On the other hand, if the concentration of the amide solvent (preferably NMP) exceeds 60 mass%, uniform coagulation cannot be performed even in the interior of the fibers, and therefore, it may also be difficult to reduce the amount of solvent remaining in the fibers. The immersion time of the fibers in the coagulation bath is preferably in the range of 0.1 to 30 seconds.

[0026] Next, the fiber is stretched at a stretch ratio of 3 to 4 in a plastic stretching bath containing an amide solvent, preferably an aqueous solution of NMP with a concentration of 45 to 60% by mass, and the bath temperature is set in the range of 10 to 50° C. After stretching, the fiber is thoroughly washed by passing it through an aqueous solution of NMP with a concentration of 20 to 40% by mass at 10 to 30° C., and then through a warm water bath at 50 to 70° C. The washed fiber is subjected to a dry heat treatment at a temperature of 270 to 290° C. According to this production method, it is possible to obtain meta-type wholly aromatic polyamide fibers that satisfy the above-mentioned ranges of the crystallinity and the amount of residual solvent.

[0027] The meta-type wholly aromatic polyamide fiber may be in the form of a long fiber (multifilament) or a short fiber. In particular, in order to blend with other fibers, a short fiber having a fiber length of 25 to 200 mm (more preferably 30 to 150 mm) is preferable. The single fiber fineness is preferably in the range of 1 to 5 dtex.

[0028] In the fabric of the present invention, the mass ratio of the meta-type wholly aromatic polyamide fiber is preferably in the range of 70 to 99 mass% (more preferably 75 to 95 mass%) relative to the mass of the fabric. If the mass ratio of the meta-type wholly aromatic polyamide fiber is smaller than this range, the flame retardancy of the fabric may decrease. Conversely, if the mass ratio of the meta-type wholly aromatic polyamide fiber is larger than this range, the mass ratio of the conductive fiber decreases, and therefore the antistatic property may decrease.

[0029] On the other hand, the conductive fiber contains a cationic dyeable polyester component. Such cationic dyeable polyester contains a cationic dye dyeable agent (such as an ester-forming sulfonic acid metal salt compound) in the polyester, and for example, polyethylene terephthalate copolymerized with 5-sulfoisophthalic acid sodium salt is suitable. When a fabric contains meta-type wholly aromatic polyamide fiber and such cationic dyeable conductive fiber, the meta-type wholly aromatic polyamide fiber and the conductive fiber are both dyed in a deep color by dyeing with a cationic dye, and the entire fabric is uniformly dyed. In this case, it is preferable that the meta-type wholly aromatic polyamide fiber and the conductive fiber are colored in the same color, and it is preferable that the hue difference between the meta-type wholly aromatic polyamide fiber and the conductive fiber is ΔE of 3 or less.

[0030] As the conductive fiber, preferred are fibers in which conductive particles (e.g., carbon or white metal) are kneaded into cationic dyeable polyester fibers, and core-sheath type composite fibers composed of a core containing conductive particles and a sheath not containing conductive particles. In particular, preferred are core-sheath type composite fibers (or eccentric core-sheath type composite fibers) in which the sheath is made of cationic dyeable polyester not containing conductive particles and the core is made of a polymer containing conductive carbon or white metal. By incorporating such conductive fibers in the fabric, static electricity caused by friction of the fabric can be reduced, and as a result, problems such as dust adhesion, harmful effects due to discharge, and ignition in explosion-proof environments can be reduced.

[0031] As the conductive particles, known conductive carbon black, conductive metal compounds, etc. can be used. Examples of carbon black include acetylene black, oil furnace black, thermal black, channel black, and ketjen black. On the other hand, as the conductive metal compounds, stannic oxide and zinc oxide, which are mainly conductive metal oxides and have excellent whiteness, are preferable. The stannic oxide referred to here includes stannic oxide containing a small amount of antimony compounds, and conductive metal composites obtained by coating the surface of titanium oxide particles with stannic oxide containing a small amount of antimony compounds. The zinc oxide also includes conductive zinc oxide in which a small amount of aluminum oxide, lithium oxide, indium oxide, etc. is dissolved. These can be used by dispersing them in a matrix polymer as a fine powder. In this case, examples of the matrix polymer include polyester, polyolefin, polyamide, etc., and the most suitable one may be appropriately selected from the viewpoints of adhesion to the cationic dyeable polyester used as the sheath component, affinity with the conductive material dispersed therein, and ease of handling. The conductive fibers can be produced, for example, by the method described in JP-A-10-310974.

[0032] In addition, the conductive fibers in the fabric of the present invention are preferably only conductive fibers containing the cationic dyeable polyester component, but may contain other conductive fibers within the scope of the present invention. Examples of other conductive fibers include acrylic fibers (acrylic core-sheath fibers or acrylic fibers kneaded with conductive particles) and fibers kneaded with conductive particles, but when other conductive fibers are contained in the fabric, acrylic fibers are preferred due to the relationship between the compatibility (dyeability) with the cationic dye and the hue difference of the meta-type wholly aromatic polyamide fibers after dyeing described above.

[0033] The conductive fibers may be in the form of long fibers (multifilament) or short fibers. In particular, short fibers having a fiber length of 25 to 200 mm (more preferably 30 to 150 mm) are preferred for blending with other fibers. The single fiber fineness is preferably in the range of 1 to 5 dtex.

[0034] In the fabric of the present invention, the mass ratio of the conductive fiber is preferably in the range of 1 to 30 mass% (more preferably 1 to 20 mass%) relative to the mass of the fabric. If the weight ratio of the conductive fiber is smaller than this range, the antistatic properties of the fabric may be reduced. Conversely, if the weight ratio of the conductive fiber is larger than this range, the mass ratio of the meta-type wholly aromatic polyamide fiber is reduced, and thus the flame retardancy may be reduced.

[0035] The fabric of the present invention may be composed of only the meta-type wholly aromatic polyamide fibers and conductive fibers, but may further contain one or more fibers selected from the group consisting of para-type wholly aromatic polyamide fibers, polyphenylene sulfide fibers, polyimide fibers, polybenzimidazole fibers, polybenzoxazole fibers, polyamideimide fibers, polyetherimide fibers, Pyromex (registered trademark), and carbon fibers.

[0036] For example, if the fabric contains para-type wholly aromatic polyamide fibers, the strength (such as tensile strength) of the fabric is improved, and this is preferable. In this case, the mass ratio of the para-type wholly aromatic polyamide fibers is preferably within the range of 1 to 10 mass% relative to the mass of the fabric.

[0037] The fabric of the present invention may further contain polyester fibers. In this case, the mass ratio of the polyester fibers is preferably within the range of 1 to 10% by mass relative to the mass of the fabric.

[0038] Here, in order to obtain a fabric that is excellent not only in flame retardancy and antistatic properties but also in appearance quality, it is preferable that these fibers are blended and contained in the fabric as a blended yarn. In this case, the fiber length of each fiber is preferably 25 to 200 mm (more preferably 30 to 150 mm). The fiber lengths of each fiber may be the same or different.

[0039] In the present invention, in order to obtain a high-quality appearance, it is preferable that the meta-type wholly aromatic polyamide fiber and the conductive fiber are both colored. It is particularly preferable that the meta-type wholly aromatic polyamide fiber and the conductive fiber are colored in the same color (ΔE of 3 or less). Here, it is preferable that the meta-type wholly aromatic polyamide fiber and the conductive fiber contain the same dye, and it is particularly preferable that the dye is a cationic dye.

[0040] Cationic dyes are water-soluble dyes that are soluble in water and have a group that exhibits basicity, and are often used for dyeing acrylic fibers, natural fibers, or cationic dyeable polyester fibers. Examples of cationic dyes include diacrylmethane-based dyes, triacrylmethane-based dyes, quinoneimine-based dyes (azine, oxazine, thiazine-based dyes), xanthene-based dyes, methine-based dyes (polymethine, azamethine-based dyes), heterocyclic azo-based dyes (thiazole azo, triazole azo, benzothiazole azo-based dyes), and anthraquinone-based dyes. In recent years, cationic dyes that have been made dispersible by blocking basic groups have also become known, and both can be used. Among these, azo-based dyes are preferred. For example, CI Basic Blue 54, CI Basic Blue 3, CI Basic Red 29, CI Basic Yellow 67, and the like can be preferably exemplified as azo-based dyes.

[0041] In the present invention, the method for producing the fabric is not particularly limited, and any known method can be used. For example, at least the meta-type wholly aromatic polyamide fiber and the conductive fiber are mixed to obtain a spun yarn.

[0042] In this case, the spun yarn fineness (count) is preferably 20 to 80 cotton count (Ecc) in terms of yarn breakage resistance and strength. The number of single fibers is preferably 60 or more. The raw cotton single fiber fineness is preferably 3.0 dtex or less (more preferably 0.001 to 3.0 dtex). The twist coefficient (first twist coefficient) of the spun yarn is preferably in the range of 3.6 to 4.2 (more preferably 3.8 to 4.0). The higher the twist coefficient, the more the fluff converges and the better the pilling resistance of the fabric, but on the other hand, the spun yarn becomes rigid and the elongation decreases, which may reduce the tear strength of the fabric or harden the fabric. The twist coefficient is expressed by the following formula. Twist factor = number of twists (twists / 2.54 cm) / cotton count of spun yarn (Ecc) 1 / 2 The spinning method of the spun yarn may be a conventional spinning method such as ring spinning, innovative spinning such as MTS, MJS, MVS, etc. The twist direction may be either Z direction or S direction.

[0043] Next, the spun yarn is optionally twist-set (vacuum steam set), and then, if necessary, two or more spun yarns (preferably 2 to 4, particularly preferably 2) are aligned and doubled and twisted. Examples of twisting machines used for doubling and twisting include up-twisters, covering machines, Italian-type twisting machines, and double twisters.

[0044] In this case, the twist direction of the double twist (first twist) is the additional twist direction. For example, when the twist direction of the spun yarn is Z-twist, the twist is performed in the same Z direction. The number of twists is preferably 2000 times / m or more, more preferably 2100 to 3000 times / m, and particularly preferably 2300 to 2800 times / m. If the number of twists is less than 2000 times / m, the spun yarn may not be in a coiled form after twist setting and untwisting.

[0045] Next, the ply-twisted yarn is subjected to twist setting (high pressure vacuum steam setting similar to that used when twist setting conventional aramid two-ply yarns). If it is necessary to impart a strong twist setting, the number of twist setting may be increased, or the twist setting temperature or setting time may be changed. For example, the setting temperature may be 115 to 125°C, the setting time may be 20 to 40 minutes, and the number of times may be 1 to 3. The higher the setting temperature and the longer the setting time, the better the setting property, which is preferable. It is possible to further improve the setting property by increasing the number of twist setting times, extending the treatment time, or raising the temperature. Considering production management (safety of work management, quality control, etc.) and production processing costs, it is preferable to extend the treatment time. In addition, the higher the degree of vacuum, the better the quality and the more preferable it is.

[0046] Next, the twist-set plied yarn is untwisted (twisted in the opposite direction to the plied twist direction) and, if necessary, heat-set. In this case, the number of twists for untwisting is preferably in the range of 70 to 90% of the number of twists for plied twist. By untwisting with a number of twists in this range, a coiled spun yarn having stretchability is obtained. In such a coiled spun yarn, the number of twists is preferably in the range of 200 to 860 turns / m to obtain excellent stretchability. The raw cotton used for the spun yarn may be dyed (yarn-dyed) raw cotton or original dyed raw cotton, or raw cotton that has been subjected to a functional treatment (such as sweat absorption, quick drying, stain resistance, flame retardancy, ultraviolet absorption, etc.).

[0047] In the fabric of the present invention, the fabric structure is not particularly limited and may be any of woven fabric, knitted fabric, and nonwoven fabric, but woven fabric is preferred in terms of flame retardancy, flame resistance, fabric strength, etc. In this case, preferred fabric structures include plain weave, twill weave, satin weave, and double weave.

[0048] In order to obtain excellent protective performance, the density of the woven fabric is preferably a warp density of 50 threads / 2.54 cm or more and a weft density of 50 threads / 2.54 cm or more (more preferably a warp density of 60 threads / 2.54 cm or more and a weft density of 60 threads / 2.54 cm or more, and particularly preferably a warp density of 60 to 80 threads / 2.54 cm and a weft density of 60 to 80 threads / 2.54 cm).

[0049] The fabric of the present invention can be knitted or woven by a conventional method using the above-mentioned spun yarn. In this case, it is preferable to weave the fabric into a twill weave, plain weave, or other structure using a rapier loom or the like using a single yarn or two-ply yarn. Knitted fabrics and nonwoven fabrics are also acceptable. It is preferable to carry out post-processing after knitting and weaving. Specific examples of post-processing steps include scouring, drying, relaxing, singeing, dyeing and functionalizing.

[0050] The dyeing process is preferably carried out in a dye bath containing the above-mentioned cationic dye. In this case, a method of dyeing at 115 to 135° C., followed by reduction and drying can be preferably adopted, but is not limited thereto. In dyeing, it is preferable to use a carrier agent, and it is preferable to perform dyeing treatment in the same bath of cationic dye and carrier agent. In addition, by treating the fabric with a special surfactant before cationic dyeing, it becomes possible to achieve deep dyeing by spread dyeing.

[0051] The carrier agent is preferably at least one selected from DL-β-ethylphenethyl alcohol, 2-ethoxybenzyl alcohol, 3-chlorobenzyl alcohol, 2,5-dimethylbenzyl alcohol, 2-nitrobenzyl alcohol, p-isopropylbenzyl alcohol, 2-methylphenethyl alcohol, 3-methylphenethyl alcohol, 4-methylphenethyl alcohol, 2-methoxybenzyl alcohol, 3-iodobenzyl alcohol, cinnamic alcohol, p-anisyl alcohol, and benzhydrol. Specific examples of the commercial product include benzyl alcohol, Dowanol PPH manufactured by Dow Chemical, and CINDYE DNK manufactured by BOZZETTO. In addition, in order to further improve the dyeability, it is preferable to use benzyl alcohol, especially 2,5-dimethylbenzyl alcohol or 2-nitrobenzyl alcohol.

[0052] Scouring and relaxation treatments may be spread-fabric treatments or liquid flow scouring and relaxation treatments. Specifically, this is a method of treatment using a spread-fabric non-tension machine in continuous scouring and continuous drying. For example, this is a method using a Softser scouring machine, dry velvet, shrink surfer, short loop, Luciole dryer, etc. In some cases, it is possible to omit the scouring and relaxation processes.

[0053] In addition, to improve other properties, the fabric may be sheared and / or singed. Furthermore, various other processes may be applied to impart functions such as sweat absorption, water repellency, heat storage, UV protection, antistatic, antibacterial, deodorant, insect repellent, mosquito repellent, phosphorescent, and retroreflective properties. The woven or knitted fabric used may be a dope-dyed product, a yarn-dyed product, or a piece-dyed product.

[0054] The sweat absorbent is preferably polyethylene glycol diacrylate or a derivative of polyethylene glycol diacrylate, a polyethylene terephthalate-polyethylene glycol copolymer, or a water-soluble polyurethane.

[0055] Examples of the method for adding a sweat absorbent to a fabric include a padding method and a method of treating the fabric in the same bath as the dyeing solution during dyeing. The thus obtained fabric preferably has a thickness of 0.30 mm or more (more preferably 0.35 to 0.50 mm). If the fabric thickness is less than 0.30 mm, sufficient antistatic properties may not be obtained. Conversely, if the fabric thickness is more than 0.50 mm, the lightness and wearing comfort may decrease.

[0056] In addition, the fabric weight is 100 to 300 g / m 2 (More preferably 120 to 260 g / m 2 If the basis weight of the fabric is smaller than this range, sufficient antistatic properties may not be obtained. Conversely, if the basis weight of the fabric is larger than this range, the lightness and wearing comfort may decrease. Since the fabric of the present invention has the above-mentioned constitution, it is excellent not only in flame retardancy and antistatic properties but also in appearance quality. In particular, the antistatic properties have excellent washing durability.

[0057] In the case where the fabric of the present invention contains a conductive cationic dyeable polyester fiber composed of a core containing conductive particles and a sheath not containing conductive particles, the conductive particles contained in the core absorb the irradiation energy of an electric arc flash and suppress the energy that penetrates the fabric, so that the fabric has excellent protective performance for the human body. Since the sheath is composed of cationic dyeable polyester not containing conductive particles, it can be dyed with the same cationic dye as the meta-type wholly aromatic polyamide fiber.

[0058] Here, the antistatic property is defined as a frictional charge of 3.5 μC / m2 measured according to JIS L1094-2014 C method. 2 Less than or equal to 0.1 to 3.0 μC / m 2 It is also important that the triboelectric charge measured by JIS L1094-2014 C method is 3.5μC / m after 25 washing cycles as specified in JIS L1930 C4 method (using JAFET standard detergent). 2 Less than or equal to 0.1 to 3.0 μC / m 2 However, acrylic and nylon should be tested and the higher value should be used.

[0059] As for flame retardancy, it is preferable that the afterflame time is 1.0 second or less in the flammability measurement specified in JIS L1091-1992 A-4 method (12 second flame contact). The dye fastness is preferably grade 3 or higher when light fastness is measured using a xenon arc lamp in accordance with JIS L0843, grade 3 or higher when washing fastness is measured according to JIS L0844 A-2 method, grade 3 or higher when sweat fastness is measured according to JIS L0848, and grade 3 or higher when friction fastness is measured according to JIS L0849.

[0060] The present invention also provides a textile product made from the above-mentioned fabric, the textile product being selected from the group consisting of protective clothing, work clothing, fireproof clothing, camouflage clothing, happi coats, and aprons. Since such textile products use the above-mentioned fabric, they are excellent in flame retardancy, antistatic properties and appearance quality. In particular, the antistatic properties have excellent washing durability. EXAMPLES

[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The physical properties in the examples were measured by the following methods.

[0062] (1) Flame retardancy of fabric The afterflame time was measured in accordance with the flammability measurement method specified in JIS L1091-1992 A-4 method (12-second flame contact).

[0063] (2) Residual Solvent Amount Approximately 8.0 g of raw fibers were collected, dried at 105°C for 120 minutes, and then allowed to cool in a desiccator, and the fiber mass (M1) was weighed. Next, the fibers were refluxed in methanol for 1.5 hours using a Soxhlet extractor to extract the amide-based solvent contained in the fibers. After extraction, the fibers were taken out and vacuum-dried at 150°C for 60 minutes, and then allowed to cool in a desiccator, and the fiber mass (M2) was weighed. The amount of solvent remaining in the fibers (amide-based solvent mass) was calculated using the obtained M1 and M2 according to the following formula. Residual solvent amount (%) = [(M1-M2) / M1] x 100

[0064] (3) Crystallinity Using an X-ray diffraction measuring device (Rigaku RINT TTRIII), the fibers were aligned into a fiber bundle with a diameter of about 1 mm and attached to a fiber sample stage to measure the diffraction profile. The measurement conditions were Cu-Kα radiation source (50 kV, 300 mA), scanning angle range 10 to 35°, continuous measurement 0.1° width measurement, and 1° / min scanning. The total scattering profile was obtained by correcting the air scattering and incoherent scattering from the measured diffraction profile using linear approximation. Next, the amorphous scattering profile was subtracted from the total scattering profile to obtain the crystalline scattering profile. The degree of crystallinity was calculated from the area intensity of the crystalline scattering profile (crystalline scattering intensity) and the area intensity of the total scattering profile (total scattering intensity) using the following formula. Crystallinity (%) = [crystal scattering intensity / total scattering intensity] × 100

[0065] (4) Stainability The color was measured using a Macbeth spectrophotometer (Color-Eye3100) to determine ΔE.

[0066] (5) Antistatic The amount of triboelectric charge was measured using JIS L1094-2014 C method. It was 3.5μC / m 2 The following were deemed acceptable. However, after testing with acrylic and nylon, the higher value was used.

[0067] (6) Weight Measured according to JIS L1096.

[0068] (7) Color fastness The light fastness was measured using a xenon arc lamp according to JIS L0843, the washing fastness according to JIS L0844 A-2 method, the sweat fastness according to JIS L0848, and the friction fastness according to JIS L0849.

[0069] (Conductive fiber) Using a known method, a conductive fiber was obtained consisting of a core-sheath type composite fiber in which the sheath was made of polyethylene terephthalate (cationic dyeable polyester) copolymerized with 5-sulfoisophthalic acid sodium salt that did not contain conductive particles, and the core was made of a polymer containing white conductive particles mainly composed of titanium oxide particles.

[0070] [Example 1] A 1 / 68 count spun yarn was produced using meta-type wholly aromatic polyamide fiber (Teijin Limited, "Teijinconex NEO" (registered trademark)), para-type wholly aromatic polyamide fiber (Teijin Aramids, trade name "Twaron") having a single fiber fineness of 1.7 dtex and a fiber length of 50 mm, and the above-mentioned conductive fiber having a single fiber fineness of 3.6 dtex and a fiber length of 51 mm, so that the composition was 93% by mass of meta-type wholly aromatic polyamide fiber, 5% by mass of para-type wholly aromatic polyamide fiber, and 2% by mass of conductive fiber, to obtain a two-ply twisted yarn.

[0071] Next, the yarn was used for all warp and weft threads to weave a plain weave fabric having a warp density of 57 threads / 2.54 cm and a weft density of 53 threads / 2.54 cm. The undyed fabric (grey) was then dyed for 60 minutes at 130°C using a liquid flow dyeing tester (Texam Giken infrared heating dyeing tester) in a dyebath containing a cationic dye (Nippon Kayaku Co., Ltd., Kayacryl Red GL-ED 1.0% owf) and a carrier agent (Dow Chemical Co., Ltd., Dowanol PPH, 40 g / L) at a temperature increased from room temperature.

[0072] The dyed fabric obtained was red in color and had good appearance quality without color unevenness. The meta-type wholly aromatic polyamide fiber and the conductive fiber were colored the same color, and the hue difference ΔE between them was 3 or less. The results of measuring the antistatic property and flame retardancy of the dyed fabric obtained are shown in Table 1.

[0073] [Comparative Example 1] An undyed woven fabric (grey fabric) was obtained in the same manner as in Example 1, except that a conductive acrylic fiber (manufactured by Mitsubishi Chemical Corporation, trade name "COREBRID", eccentric core-sheath type conductive acrylic fiber consisting of sheath: acrylic / core: conductive carbon-containing polymer) having a single fiber fineness of 3.3 dtex and a fiber length of 38 mm was used as the conductive fiber.

[0074] The undyed fabric (grey) was then dyed for 60 minutes at 130°C using a liquid flow dyeing tester (Texam Giken infrared heating dyeing tester) in a dyebath containing a cationic dye (Nippon Kayaku Co., Ltd., Kayacryl Red GL-ED 1.0% owf) and a carrier agent (Dow Chemical Co., Ltd., Dowanol PPH, 40 g / L) at a temperature increased from room temperature.

[0075] The obtained dyed fabric was red and had good appearance quality without color unevenness. In addition, the meta-type wholly aromatic polyamide fiber and the conductive fiber were colored the same color, and the hue difference ΔE between the two was 3 or less. However, it could not be said that the antistatic property was sufficient. The measurement results are shown in Table 1.

[0076] [Table 1] [Industrial Applicability]

[0077] The present invention provides fabrics and textile products which are excellent in flame retardancy, antistatic properties and appearance quality, and is of extremely great industrial value.

Claims

1. A fabric comprising a meta-type wholly aromatic polyamide fiber and a conductive fiber, the conductive fiber containing a cationic dyeable polyester component, the meta-type wholly aromatic polyamide fiber and the conductive fiber being both colored, and a triboelectric charge amount measured by JIS L1094-2014 C method of 3.5 μC / m 2 A fabric characterized in that:

2. 2. The fabric according to claim 1, wherein the conductive fiber is a core-sheath type composite fiber, and in the core-sheath type composite fiber, the core contains conductive particles, and the sheath is made of a cationic dyeable polyester that does not contain conductive particles.

3. The fabric of claim 1 , wherein the meta-type wholly aromatic polyamide fiber and the conductive fiber contain the same dye.

4. The fabric of claim 3 , wherein the dye is a cationic dye.

5. The fabric according to claim 1, wherein the conductive fibers are contained in the fabric in an amount of 1 to 30 mass% based on the mass of the fabric.

6. The fabric according to claim 1 , wherein the meta-type wholly aromatic polyamide fiber and the conductive fiber are contained in the fabric as a blended yarn.

7. Fabric weight is 100-300g / m 2 The fabric of claim 1 , wherein the elastic modulus is in the range of

8. After 25 washes as specified in JIS L1930 C4 method, the amount of triboelectric charge measured by JIS L1094-2014 C method was 3.5 μC / m 2 2. The fabric of claim 1 , wherein:

9. The fabric according to claim 1, which has an afterflame time of 1.0 second or less in a flammability measurement specified in JIS L1091-1992 A-4 method (12 second flame contact).

10. 10. A textile product comprising the fabric according to claim 1, selected from the group consisting of protective clothing, work clothing, fireproof clothing, camouflage clothing, happi coats, and aprons.

Citation Information

Patent Citations

  • Colored organic fiber, fabric and clothing and method for manufacturing fabric

    WO2015159749A1

  • Fabric and fiber product

    WO2016035638A1

  • Fabric, method for manufacturing same, and fiber product

    WO2018084040A1

  • Cloth and protective product

    WO2020129746A1